2007
DOI: 10.1159/000109634
|View full text |Cite
|
Sign up to set email alerts
|

Two independent chromosomal rearrangements, a very small (550 kb) duplication of the 7q subtelomeric region and an atypical 17q11.2 <i>(NF1)</i> microdeletion, in a girl with neurofibromatosis

Abstract: Most patients with neurofibromatosis (NF1) are endowed with heterozygous mutations in the NF1 gene. Approximately 5% show an interstitial deletion of chromosome 17q11.2 (including NF1) and in most cases also a more severe phenotype. Here we report on a 7-year-old girl with classical NF1 signs, and in addition mild overgrowth (97th percentile), relatively low OFC (10th–25th percentile), facial dysmorphy, hoarse voice, and developmental delay. FISH analysis revealed a 17q11.2 microdeletion as well as an unbalanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
6
0
2
Order By: Relevance
“…These results provide preliminary evidence that the clinical phenotypes associated with 7q36.3 duplications may include pediatric neurodevelopmental disorders such as autism, but do not include bipolar disorder. Also worthy of note, larger chromosomal abnormalities involving 7q have been reported in association with neurodevelopmental disorders, including deletions of 7q36-7qter 9,10 and duplications of 7q35-7qter 11 ; a 550 kb duplication of 7qter (of unknown clinical relevance) has been reported in a patient with neurofibromatosis 12 .…”
mentioning
confidence: 97%
“…These results provide preliminary evidence that the clinical phenotypes associated with 7q36.3 duplications may include pediatric neurodevelopmental disorders such as autism, but do not include bipolar disorder. Also worthy of note, larger chromosomal abnormalities involving 7q have been reported in association with neurodevelopmental disorders, including deletions of 7q36-7qter 9,10 and duplications of 7q35-7qter 11 ; a 550 kb duplication of 7qter (of unknown clinical relevance) has been reported in a patient with neurofibromatosis 12 .…”
mentioning
confidence: 97%
“…We determined VIPR2-LCR orientation on three sets of anonymous DNA samples: (a) parental samples from 324 anonymized parent/child triplets selected from a cohort of healthy Italian subjects previously collected for epidemiological studies on mental health in youth; (b) 937 randomly selected samples, among which: 243 anonymous blood donors; 263 anonymous university students; 257 anonymous clinical left-over blood samples; 174 anonymized subjects from a second cohort collected for epidemiological studies of mental health in youths; and (c) 64 EBV lines from European (20), Asian (20) and African (28) subjects obtained from the Coriell repository. The overwhelming majority of subjects in sets (a) and (b) is expected to be unrelated and of Italian ancestry.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, these two families share one novel WDR60 missense mutation, although haplotype analysis suggested no shared ancestry. In another study, it was found that duplication of the subtelomeric region of chromosome 7q containing functional genes (FAM62B, WDR60, and VIPR2) can be tolerated without phenotypic consequences (Bartsch et al, 2007). Lack of one allele of WDR60 is also asymptomatic (Perche et al, 2013).…”
Section: Ift Dynein and Human Diseasesmentioning
confidence: 99%